PENGARUH PERMAINAN TRADISIONAL TERHADAP PHYSICAL LITERACY SISWA MENENGAH PERTAMA - Resi Mustika Rasnita; Andika Triansyah; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to increase the success of students in carrying out physical activities or called physical literacy by learning traditional games for students. This study uses descriptive quantitative analysis with experimental research methods and this research design uses a one group pre-test-post-test design.The subjects of this study were students.Data collection using a questionnaire.The data analysis technique used t-test analysis, through the prerequisite tests for normality and homogeneity.The results of hypothesis testing using the t-test get a t-count of 3.702 which is greater than the t-table of 1.699 (3.702 > 1.699), so there is a significant difference between the data before and after being given treatment. The increase in the average was evident because there was an increase of 8 from 54.00 to 62.00. If described as a percentage, the increase is 14.81%. Thus, it can be concluded that there is an influence of traditional games on the physical literacy of the students.Keywords: Physical Literacy, Traditional Games